STRESS AND STRAIN BEHAVIOUR OF REINFORCED CONCRETE ANISOTROPIC SHELLS - Gaponova, L. V.; Grebenchuk, S. S. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The character changes deflected mode of «Monofant» system fragments. For experimental studies state snippets new structural system of “Monofant” multi conformity was deformed and method based on hydrostatic load when the load is given by the weight of water, was used, and its value is governed by the height of the water column. To determine the qualitative and quantitative research object deformation measurements displacement cylindrical and spherical shells in 25 points was carried. However, the configuration structure complexity was given, which in turn led to the emergence of both vertical and horizontal movements of the studied surface shell under vertical load, the need to measure movements in two directions in a cylindrical shell of vertical displacement and a spherical shell. The study shows that the structural elements are endowed with all the necessary strength characteristics and attributes rigidity bearing elements of reinforced concrete buildings.